2021
DOI: 10.1111/1440-1681.13594
|View full text |Cite
|
Sign up to set email alerts
|

Renalase—A new understanding of its enzymatic and non‐enzymatic activity and its implications for future research

Abstract: Renalase was first described in 2005 by the research team of Gary V.Desir who aimed to find additional proteins that may be involved in endocrine function of the kidneys. 1 To do so, the scientists searched the Mammalian Gene Collection (MCG) for genes that: encode proteins, have <20% sequence similarity to known proteins, contain a signal peptide sequence and do not contain transmembrane domains. Their initial search identified 114 candidate genes encoding novel secretory proteins; however, in further Norther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 44 publications
(123 reference statements)
0
9
0
Order By: Relevance
“…Some ROSs such as superoxide radicals and H2O2 can be made after a respiratory burst via neutrophil cells. Ultimately, oxidative stress is developed by this mechanism which is related to the cytokine storms and blood clots in patients with COVID-19 [89] , [90] .…”
Section: Immune Response In Sars-cov-2mentioning
confidence: 99%
“…Some ROSs such as superoxide radicals and H2O2 can be made after a respiratory burst via neutrophil cells. Ultimately, oxidative stress is developed by this mechanism which is related to the cytokine storms and blood clots in patients with COVID-19 [89] , [90] .…”
Section: Immune Response In Sars-cov-2mentioning
confidence: 99%
“…In addition, few studies have investigated the relationship between polymorphisms in the RNLS and hypertension in humans; however, findings are conflicting and limited to many factors [ 36 ]. SNP rs2576178 and rs2296545 within the RNLS gene were associated with essential hypertension among 2586 Chinese individuals [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…In short, renalase is a scavenger enzyme that protects cells against the accumulation of substances that may negatively affect other enzymatic reactions. However, these assumptions are not based on human studies and it is yet to be established whether human enzymes are prone to inhibition by isomeric forms of β-NAD(P)H. We have discussed enzymatic and non-enzymatic activity of renalase in our previous work [ 13 ]. In this study, we have found a positive linear relationship between renalase blood concentration and TAS level which seems to confirm renalases’ antioxidant properties.…”
Section: Discussionmentioning
confidence: 99%
“…The data on renalase’s involvement in redox balance in humans is scarce. We have discussed recent findings on renalase’s enzymatic and non-enzymatic activity in our previous work [ 13 ].…”
Section: Introductionmentioning
confidence: 99%